The current evidence on diagnosis and treatment of acute aortic syndrome - Minegishi, Shintaro; Watanabe, Hiroki; Horita, Nobuyuki; Shibata, Yuji; Kaneko, Takeshi; Ishigami, Tomoaki (Journal of Thoracic Disease, 2016)
In their article titled “Acute Aortic Dissection and Intramural Hematoma: A Systematic Review” Mussa et al. highlight the important evidence on diagnosis and treatment of acute aortic syndrome (AAS) (1). AAS describes the presentation of patients with one of a number of life threatening aortic pathologies, including aortic dissection (AD), intramural hematoma (IMH), and penetrating atherosclerotic ulcer (PAU).